The interactive library as a virtual working space - Degkwitz, Andreas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
The internet and the new digital media are challenging the traditional business model of academic libraries and enable new capabilities of information provisioning and new shapes of collaborations between the librarians and the users. To pick up the demands and the expectations of the many users, whose information behavior is heavily influenced by the internet, a new business model for academic libraries has to be designed urgently. The aim of the project is to analyze and to identify the organizational and technical requirements of a business model for the future library, which is based on the potential of the internet and the new media. The result is a pilot study about the interactive, multi-user driven library as the future business model for libraries.